Traditional Word Guess Game Development âDor-DoranâAs An Integrated Learning Media In The Third Class Of Madiun Islamiyah Islamic Elementary School. - Tryanasari, Dewi (978-602-7561-892)
Elementary school children has three main features such as concrete, integrative, and hierarchycal. Untuk memfasilitasi anak belajar sesuai dengan karakteristiknya, perlu rancangan pembelajaran terpadu dan nyata. To facilitate the students to learn accordance with their characteristics, needs to design an integrated learning and real learning. Di kelas III Madrasah Ibtidaiyah Islamiyah Kota Madiun (MIIKM) pembelajaran terpadu telah diterapkan namun kurang menarik.Siswa MIIKM senang bermain. In the third clasa of Madiun Islamiyah Islamic Elementary School (MIIKM) integrated learning has been applied, but less interesting. The students of MIIKM like playing something. Untuk itu media yang bisa digunakan secara langsung dalam pembelajaran adalah permainan âDor-doranâ.thatâs why the media can be used directly in the learning is a game of "Dor-Doranâ. Permainan ini bisa memadukan beberapa kompetensi dasar dan menyenangkan bagi siswa.This game can match some basic competence and be fun for students. Berdasarkan uraian tersebut dilakukan penelitian yang bertujuan untuk: (1) mendeskripsikan pengembangan media pembelajaran terpadu di kelas III MIIKM yang berbasis permainan tebak kata tradisional âDor-doranâ, (2) mendeskripsikan kualitas media permainan tebak kata tradisional âDor-doranâ pada pembelajaran terpadu di kelas III MIIKM, (3) mendeskripsikan implementasi permainan tebak kata tradisional âDor-doranâ sebagai media pembelajaran terpadu di kelas III MIIKM, (4) mendeskripsikan faktor penghambat dan pendukung yang ditemukan pada pembelajaran terpadu di kelas III MIIKM dengan menggunakan media permainan tebak kata tradisional âDor-doranâ. Based on the description is conducted the research aimed at: (1) describe the development of an integrated instructional media in the third class of MIIKM based on the traditional word guess game"Dor-Doran", (2) describe the quality of traditional words guess game "Dor-Doran" at an integrated learning media in the third class of MIIKM, (3) describe the implementation of the traditional word guess game "Dor-Doran" as an integrated learning media in the third class of MIIKM, (4) describe the obstacle and support factor found at integrated learning in the third class of MIIKM using traditional word guess game "Dor-Doran."Prosedur penelitian dilakukan melalui dua tahap, yaitu pengembangan perangkat pembelajaran dan ujicoba perangkat. Â Â Â Â Â Â Â Â Â Â  Research procedures are carried out in two steps, namely the development of learningÂ  and testing devices. Objek penelitian pengembangan adalah perangkat pembelajaran yang dikembangkan, dan subjek uji coba perangkat pembelajaran adalah sepuluh orang siswa kelas III A dan 30 orang siswa kelas III B MIIKM. The object of development research is a learning devices developed, and the subject of learning device testing is a learning devices developed and the subject of learning device testing is 10 students in III A and 30 students in III B of MIIKM. Learning device is developed to refer in the development model of Dick and Carey.The results of research shows that: (1) the development process is accordance with Dickâs and Careyâs model and produce learning device in terms of content, format and language is good; (2) the quality of traditional guess word game âDor-Doranâ as integrated learning media is good, (3) the implementation of usage device is showed from feasibility of RPP, students respon, teachers activity and students activity is very goodÂ  (4) obstacle factor can be handled by teacher while suport factor found is studentâs experience with playing device without interacting with friend who become an interesting learning.Â